2005
DOI: 10.1126/science.1104345
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes-a Matter of ß-Cell Life and Death?

Abstract: In type 2 diabetes, the beta cells of the pancreas fail to produce enough insulin to meet the body's demand, in part because of an acquired decrease in beta-cell mass. In adults, pancreatic beta-cell mass is controlled by several mechanisms, including beta-cell replication, neogenesis, hypertrophy, and survival. Here, I discuss evidence supporting the notion that increased beta-cell apoptosis is an important factor contributing to beta-cell loss and the onset of type 2 diabetes. Interestingly, a key signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

14
675
2
33

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 856 publications
(724 citation statements)
references
References 50 publications
14
675
2
33
Order By: Relevance
“…FCCM contains a variety of metabolites and signalling molecules, including known adipocytokines such as leptin, adiponectin, IL-6, TNF-α and resistin. However, these adipocytokines are not thought to mediate beta cell proliferation [5,38,39]. In addition to these known adipocytokines, Wnt signalling molecules are secreted by adipocytes [9,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FCCM contains a variety of metabolites and signalling molecules, including known adipocytokines such as leptin, adiponectin, IL-6, TNF-α and resistin. However, these adipocytokines are not thought to mediate beta cell proliferation [5,38,39]. In addition to these known adipocytokines, Wnt signalling molecules are secreted by adipocytes [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms linking obesity and insulin resistance to hyperinsulinaemia and beta cell hyperplasia are incompletely understood [3]. Adipocytes are hormonally active and adipocytokines are able to elicit a response from beta cells [5]. Studies have shown that adipocytes secrete Wnt signalling molecules to regulate adipocyte differentiation [9][10][11].…”
mentioning
confidence: 99%
“…This finding suggests that subtle increases in HH signalling might induce a decrease in beta cell mass. A decrease in beta cell mass is a typical feature of the onset of type 2 diabetes [35,36]. Thus, we investigated the glucose tolerance and beta cell mass in our Ptch1 +/mes and Ptch1 +/− mice after adjusting for genetic background.…”
Section: Discussionmentioning
confidence: 99%
“…However, in individuals destined to develop type 2 diabetes, pancreatic beta cells fail to produce enough insulin to meet systemic demand. This beta cell failure is caused by insufficient beta cell response to glucose and inadequate beta cell mass expansion [1]. Recently, several reports have convincingly confirmed the contribution of beta cell mass reduction to type 2 diabetes [2,3], at least in its advanced stages.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several reports have convincingly confirmed the contribution of beta cell mass reduction to type 2 diabetes [2,3], at least in its advanced stages. Although the cause of this decrease is unknown, increased apoptosis may play an important role [1,2]. In addition to genetic factors, processes involving glucotoxicity and/or lipotoxicity are likely to be contributory [4].…”
Section: Introductionmentioning
confidence: 99%